P82 Critical discourse analysis of the joint committee meetings on the eighth amendment of the constitution of ireland. (3rd September 2019) - Shiplo, S; O'Donoghue, K; Meaney, S
Abstract : Background: The 1983 Eighth Amendment to the Irish Constitution stated that the right to life of a pregnant mother and her unborn were equal, which meant that pregnancy terminations were illegal in Ireland. Ongoing debate surrounding strict pregnancy termination laws compelled the Irish government to form a committee tasked with deliberating the arguments for and against repealing the Eighth Amendment as well as forming recommendations. The objective of this study is to evaluate the issues raised and how information was presented during the joint committee meetings on the Eighth Amendment. Methods: Published transcripts from the Joint Committee on the Eighth Amendment of the Constitution meetings were accessed online for analysis. The committee's deliberations commenced on September 20, 2017 and concluded on December 14, 2017. This qualitative study applied a critical discourse analysis, which evaluates language in its social and cultural context. Critical discourse analysis allows for the deconstruction of language to gain an insight and understanding of socially produced meanings, recognising the ability for language to perpetuate inequalities and power dynamics. Results: Seven themes were identified from the meetings' contents related to pregnancy termination: including fatal fetal anomalies, rape and incest, decriminalisation, mental health, human rights, risk and practical issues. Throughout proceedings research evidence was often misrepresented and distorted in order to spin findings in support of members' arguments. Anecdotal evidence, including emotionally-laden narratives, was used to persuade members with divergent views to change their political and ideological opinions about what is socially desirable and acceptable. When discussing the risk and practical issues of introducing termination of pregnancy, the matter of conscientious objection and maternity hospitals whose governance are influenced by religious ethics were debated, clearly illustrating the influence of cultural and religious ideologies over the health of the population. Conclusion: The framing of the discourse throughout the meetings likely influenced the committee members' knowledge, perception, and understanding of key issues, consequently impacting the development of the pregnancy termination legislation introduced in 2019. This study demonstrates that healthcare is influenced by the political context and prevailing religious ideologies in Ireland. This study reveals the potential for underlying bias in political structures to sway healthcare legislation, which can impact health and in particular women's reproductive health.